Commentary on the General Comment on article 22 of the African Charter on the Rights and Welfare of the Child: ‘Children in Conflict Situations’ (African Human Rights Yearbook / Annuaire Africain des Droits de l’Homme, 2023)
The General Comment on article 22 of the African Charter on the Rights and Welfare of the Child is intended to guide and enlighten state parties on the interpretation and application of this provision. Based on the latter, this GeneralComment examines the obligations of states in times of armed conflict, tension and civil unrest. However, the text of the General Comment poses some problems which may not facilitate its interpretation and application by state parties. Using a doctrinal approach, this study reveals that the General Comment under consideration is oriented more towards the legal implications of international human rights law than of international humanitarian law. This appears to be a remarkable contradiction in light of the aim of this General Comment to pay a particular attention to international humanitarian law. Similarly, the General Comment does not always succeed in establishing clearly and distinctly the legal implications of the obligations of states Parties depending on whether the issue is contemplated under international law or international human rights law. Moreover, the rules and concepts involved are examined without a full consideration of the development of case law, state practice and doctrine.